The Roots of Lithuanian Existentialism - Genzelis, Bronislovas (Problemos, 1988)
The circumstances of the appearance of existentialism in Lithuania are discussed in the article. The main attention is paid to the philosophical papers of Juozas Gimius written in the earlier period of his work.